A Cosmological Model With Second Law Of Thermodynamics In F(R, T) Gravity - Tiwari, R. K.; Bharali, J.; Chetry, B.; Beesham, A.
In the context of f (R, T ) modified gravity theory, we investigate a cosmological model with homogeneous and anisotropic properties, specifically the Locally Rotationally Symmetric (LRS) Bianchi type-I model. В рамках модифицированной теории гравитации f R, T  исследована космологическая модель с однородными и анизотропными свойствами, в частности, локально вращательно-симметричная (LRS) модель Бьянки типа I.
Keywords: Astrophysics